2014
DOI: 10.1101/lm.027326.112
|View full text |Cite
|
Sign up to set email alerts
|

The less things change, the more they are different: contributions of long-term synaptic plasticity and homeostasis to memory

Abstract: An important cellular mechanism contributing to the strength and duration of memories is activity-dependent alterations in the strength of synaptic connections within the neural circuit encoding the memory. Reversal of the memory is typically correlated with a reversal of the cellular changes to levels expressed prior to the stimulation. Thus, for stimulus-induced changes in synapse strength and their reversals to be functionally relevant, cellular mechanisms must regulate and maintain synapse strength both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 141 publications
(217 reference statements)
0
16
0
Order By: Relevance
“…The association between alterations in the structure and/or number of synapses and memory storage has led to numerous studies regarding the signaling pathways that might couple molecular changes to structural changes. In addition, parallel homeostatic mechanisms have been identified that can trigger synaptic scaling, which serves to stabilize the strengthened synapses while weakening or eliminating other synapses, thus providing specificity during memory consolidation (Bourne and Harris 2011;Schacher and Hu 2014).…”
mentioning
confidence: 99%
“…The association between alterations in the structure and/or number of synapses and memory storage has led to numerous studies regarding the signaling pathways that might couple molecular changes to structural changes. In addition, parallel homeostatic mechanisms have been identified that can trigger synaptic scaling, which serves to stabilize the strengthened synapses while weakening or eliminating other synapses, thus providing specificity during memory consolidation (Bourne and Harris 2011;Schacher and Hu 2014).…”
mentioning
confidence: 99%
“…From the neural perspective, a wealth of information exists regarding how neurons and circuits maintain target levels of activity despite removing or enhancing activity inputs (termed homeostatic plasticity). However, models to study these processes use pharmacological or pathological paradigms to manipulate neuronal activity in vivo and in vitro primarily at early developmental stages (Hengen et al, 2013;Knogler et al, 2010;Ngodup et al, 2015;Schacher and Hu, 2014;Turrigiano, 2012;Wilhelm and Wenner, 2008). Thus, the bullfrog respiratory control system following overwintering offers a powerful ability to uncover mechanisms leading to and resulting in the preservation (respiratory motor output and hypoxia sensitivity) and deterioration (CO 2 sensitivity) of sensorimotor function in the same species, individual and neural control system after ecologically relevant inactivity.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Hebbian plasticity at individual synapses) in order to normalise overall activity levels and prevent extrema (for review see: GuzmanKarlsson et al (2014); Schacher and Hu (2014); Yin and Yuan (2015)). Homoeostatic mechanisms are induced by and utilize mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…primary excitatory pathway in vertebrate brain) (Schacher and Hu, 2014). Insects, however, use acetylcholine as their primary excitatory neurotransmitter (Breer and Sattelle, 1987).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation